Investigations on the presence of e.coli o157:h7 in some meat products - Duygu Balpetek; Ümit Gürbüz (Eurasian Journal of Veterinary Sciences)
Aim: Presence of E. coli 0157:H7 was investigated in some meat products. Materials and Methods: Sausage, salami, hamburger meat, Inegöl meat ball, pastrami, minced meat and brisket and haunch of poultry collected from different meat sellers in Konya were used as materials. Totally 173 samples were assessed for coliform bacteria E. coli, E.coli O157 and E. coli O157:H7. Results: The average amount of coliform bacteria in frozen and refrigerated hamburger and Inegöl meatballs and sucuk, sausage, brisket and haunch meat from poultry are determined as 13;3.75;4.44; 5.10; 3.44; 1.85; 3.11; 3.14 and 4.28 log10 cfu/g, respectively. The number of E. coli bacteria in analyzed samples was found between 1.15 and 3.17 log10 cfu/g and found statistically significant (p<0.05). No proliferation was determined in sausage, salami and pastrami samples. It was found that the lowest values were in poultry haunch samples (1.15 log10 cfu/g), the highest levels were in minced meat (3.17 log10 cfu/g). In four of the minced meat samples analyzed in this study, E.coli O157 (11.1%) was determined, in two of them E.coli O157:H7 (8.1%) and in one refrigerated hamburger meat ball sample E.coli O157 and E.coli O157:H7 (4.34%) were determined. Conclusion: The presence of E.coli O157 and E.coli O157:H7 in minced meat and refrigerated hamburger meat indicates that, these products have low microbiological quality and threaten public health.